Phase II study of de‐intensified intensity‐modulated radiotherapy and concurrent carboplatin/5‐fluorouracil in lateralized p16‐associated oropharyngeal carcinoma. Issue 12 (31st August 2020) - Bahig, Houda; Lambert, Louise; Filion, Edith; Soulières, Denis; Guertin, Louis; Ayad, Tareck; Christopoulos, Apostolos; Bissada, Eric; Alizadeh, Moein; Bélair, Manon; Nguyen‐Tan, Phuc Felix
Abstract: Purpose: To assess cancer control and patient‐reported outcomes (PROs) after de‐intensified intensity‐modulated radiotherapy (IMRT) in lateralized p16‐associated oropharyngeal cancer (p16‐OPC). Methods: Lateralized p16‐OPC treated with radiotherapy and concurrent Carboplatin/5‐fluorouracil between 2011 and 2014 were enrolled. De‐intensified IMRT consisted in elective neck dose of 43.2 Gy/24 fractions and omission of contralateral retropharyngeal/level IV nodes. PROs were assessed using the EORTC QLC‐C30 and QLQ‐HN35 scales. Results: Twenty‐nine patients were included. Median follow‐up was 44 months. As per AJCC 7th Ed, 7%, 83% and 10% of patients had stage III, IVa and IVb. 5‐year locoregional control and overall survival rates were 100% and 100%, respectively. Rates of acute were 52% and 35%, respectively. At 2 years post‐treatment, 50% and 14% of patients had grade 1 xerostomia and dysgueusia, respectively. Most PROs scores returned to baseline within 8 months post‐treatment. Conclusion: De‐intensified IMRT was associated with excellent cancer outcomes, and rapid recovery of PROs in lateralized p16‐OPC.